2005
DOI: 10.1111/j.1523-1755.2005.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II induces fibronectin expression in human peritoneal mesothelial cells via ERK1/2 and p38 MAPK

Abstract: These results indicate the potential importance of ERK1/2 and p38 MAPK signaling pathways in Ang II-induced fibronectin expression in HPMC, and suggest the therapeutic potential of AT1 receptor blockers in the prevention or treatment of peritoneal fibrosis in patients on peritoneal dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 39 publications
1
55
0
Order By: Relevance
“…Western blotting was performed as described previously. 27,28 The blots were incubated overnight at 41C with antiTGFbR-I antibody (1:1000 dilution) followed by washing and incubation with HRP-conjugated goat anti-rabbit IgG antibody (1:5000 dilution). Monoclonal anti-a tubulin antibody was used as the internal control for the analysis of TGFbR-I expression.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Western blotting was performed as described previously. 27,28 The blots were incubated overnight at 41C with antiTGFbR-I antibody (1:1000 dilution) followed by washing and incubation with HRP-conjugated goat anti-rabbit IgG antibody (1:5000 dilution). Monoclonal anti-a tubulin antibody was used as the internal control for the analysis of TGFbR-I expression.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In this context, it has been demonstrated that AngII induces the expression of TGF-␤ and fibronectin in MC and that inhibitors of angiotensin-converting enzyme and AngII type 1 receptor attenuate the production of VEGF in these cells. 29,45 In addition, it was previously shown that intraperitoneal administration of an inhibitor of angiotensin-converting enzyme attenuated structural and functional alteration of the peritoneum in a rat PD model. 46 It should be taken into consideration that EMT of MC is a physiologic process that is necessary for wound healing during the aggression of the peritoneal membrane induced by PD; therefore, it is plausible that chronic blockade of EMT would result in inefficient tissue repair.…”
Section: Therapeutic Intervention On Emtmentioning
confidence: 99%
“…16 Along with TGF-␤, other proinflammatory and profibrotic cytokines as well as angiotensin II (AngII) have been shown to be upregulated during peritonitis episodes and may contribute in the setting of peritoneal fibrosis. 8,29 In regard to peritoneal angiogenesis, it has been shown that local production of the proangiogenic and vasoactive factor VEGF during PD plays a central role in increased solute transport across the peritoneum and ultrafiltration failure. 13,30,31 The most important factor of the PD solutions that are responsible for peritoneal deterioration seems to be glucose degradation products, which, through the formation of advanced glycation end products (AGE), stimulate the production of (ECM) components as well as the synthesis of cytokines and growth factors, including TGF-␤ and VEGF.…”
Section: Major Mediators Of Peritoneal Membrane Deteriorationmentioning
confidence: 99%
“…The local renin-angiotensin-aldosterone system (RAAS) is thought to play a role in peritoneal injury in PD patients [41]. Peritoneal mesothelial cells have been observed to express angiotensinogen, angiotensin-converting enzyme (ACE), and angiotensin II type 1 receptors (AT1R) [42,43]. We found that MRs were expressed by rat fibroblasts and scraped peritoneum.…”
Section: Scraping Modelmentioning
confidence: 87%